THE ACCELERATION OF MASSIVE VACCINATION ACTIVITIES IN OVERCOME CREDIT CRUNCH DURING THE COVID-19 PANDEMIC (HUMAN RIGHTS PERSPECTIVE HUMAN AND MAQASHID SHARIA): Massive Vaccination in Overcoming Credit Crunch, Human Rights Perspective on Vaccination Activities , Maqashid Syari'ah Perspective on Vaccination Activities - Wibowo, Teguh Setiawan (I-Economics, 2023)
Based on CNN Indonesia's economic growthIndonesia minus 2.2% in 2020 so that causes revenuesociety declines, corporate performance weakens due to depressed sales and production,as well as investments that are still not improving. In addition, on the supply side the risk of failurepay is very large so indirectly bad credit (credit crunch) as wellincrease. The firm level data method shows that during 2020, credit occurredcrunch caused by both demand and supply sides of credit. Actually Bank Indonesia already has a solution to overcome the credit crunch by dividingseveral subsectors into 4 quadrants of the subsectors that have the most resiliencestrong to sub-sectors that have the weakest resilience. But such a solutiononly temporary (temporary) and will not be able to overcome the problemcomprehensive credit crunch. Save the writer, the acceleration of massive vaccination activitiesis the only way that can be used to solve the problemcredit crunch. Even so, there are still many people who refusein human rights and religious arguments. Therefore, this research aims toproves that the credit crunch can only be overcome by accelerating activitiesvaccination, vaccination does not conflict with human rights values, andVaccination does not conflict with religious values, especially Islam and Religionin line with maqashid syari'ah. Key Words:“Vaccination, Credit Crunch, Human Right, Maqashid Syari’ah”